Stratification and recovery time jointly shape ant functional reassembly in a neotropical forest - Hoenle, Philipp O; Staab, Michael; Donoso, David A; Argoti, Adriana; Blüthgen, Nico (The Journal of animal ecology, 2023)
Microhabitat differentiation of species communities such as vertical stratification in tropical forests contributes to species coexistence and thus biodiversity. However, little is known about how the extent of stratification changes during forest recovery and influences community reassembly. Environmental filtering determines community reassembly in time (succession) and in space (stratification), hence functional and phylogenetic composition of species communities are highly dynamic. It is poorly understood if and how these two concurrent filters-forest recovery and stratification-interact. In a tropical forest chronosequence in Ecuador spanning 34 years of natural recovery, we investigated the recovery trajectory of ant communities in three overlapping strata (ground, leaf litter, lower tree trunk) by quantifying 13 traits, as well as the functional and phylogenetic diversity of the ants. We expected that functional and phylogenetic diversity would increase with recovery time and that each ant community within each stratum would show a distinct functional reassembly. We predicted that traits related to ant diet would show divergent trajectories reflecting an increase in niche differentiation with recovery time. On the other hand, traits related to the abiotic environment were predicted to show convergent trajectories due to a more similar microclimate across strata with increasing recovery age. Most of the functional traits and the phylogenetic diversity of the ants were clearly stratified, confirming previous findings. However, neither functional nor phylogenetic diversity increased with recovery time. Community-weighted trait means had complex relationships to recovery time and the majority were shaped by a statistical interaction between recovery time and stratum, confirming our expectations. However, most trait trajectories converged among strata with increasing recovery time regardless of whether they were related to ant diet or environmental conditions. We confirm the hypothesized interaction among environmental filters during the functional reassembly in tropical forests. Communities in individual strata respond differently to recovery, and possible filter mechanisms likely arise from both abiotic (e.g. microclimate) and biotic (e.g. diet) conditions. Since vertical stratification is prevalent across animal and plant taxa, our results highlight the importance of stratum-specific analysis in dynamic ecosystems and may generalize beyond ants.
Keywords: Animals; Forests; biodiverzita; community weighted means; Ants; lesy; Formicidae; Ecuador; functional traits; Phylogeny; chronosequence; Chocó; Biodiversity; phylogeny; ekosystém; Ecosystem; zvířata; environmental filters; fylogeneze; forest regeneration